Lump-sum transfers for agriculture, support services, and household decision making - Ambler, Kate; de Brauw, Alan; Godlonton, Susan (CGIAR System Organization, 2023)
We study the impact of one-season transfers framed for agricultural investment combined with agricultural support services on decision making among smallholder households in Senegal and Malawi using data from randomized control trials. In Senegal, we find evidence that the program increased the decision power of male household heads at the expense of other males in the household after two years. We cannot disentangle the impacts of the farm planning program and the lump sum transfer that comprised that program. In Malawi, we observe that over two years male program recipients exhibit increased decisionmaking power, while male non-recipients see reductions in decision-making power. These results are broadly due to both the transfers and the intensive agricultural support services. Changes in decision power seem to flow not just from control of income, but also from shifting household norms linked to program participation. Only in Malawi do we note some suggestive evidence that decision making power increases among female program recipients.